Evaluation on Isolates of Lignochloritic Bacteria as Probiotics of Broilers - Indah Prihartini; Lili Zalizar (Journal Animal Research and Applied Science, 2019)
The research objective was to produce a product assembly and feed technology and natural additives to improve food quality and sustainable food security. The results of the first year obtained isolates of lactic acid bacteria and lignochloritic bacteria that have potential as probiotics for livestock, namely growth, high production, and enzyme activity. Isolates of lignochloritic bacteria grow well in the intestine, but lower in the gizzard and ventricles. Isolates as probiotics tend to increase feed intake, growth, the production of eggs, meat and egg protein but lower feed conversion, meat fat, and egg cholesterol.Key words: feed additive, food additive, probiotic, antibiotic, antioxidant